PENGARUH PENDEKATAN KETERAMPILAN PROSES DASAR TERHADAP HASIL BELAJAR IPA KELAS VIII SMPNEGERI 11 YOGYAKARTA - Erni Suryandari; Hidayati Hidayati; Sigit Sujatmika (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2015)
This study descriptively aims to identify the outcomes of the learning of IPA which was used the basic skill approach and expository approach on the students in 8th of SMPN 11 Yogyakarta in academic year 2015/2016. Comperatively to determine the difference of the IPA learning outcomes between the basic skill approach and expository approach on the students in 8th of SMPN 11 Yogyakarta in academic year 2015/2016. This study belongs to Quasi experiment. The result of this study descriptively showed that the tendency of the learning outcomes used basic skill approach was the highest category and the learning outcomes which was used expository approach belongs to the high category. Comperatively there was a significance difference of the IPA learning outcomes between the learning used basic skill approach and expository approach. The average of the learning outcomes that used basic skill approach was higher than expository approach. It means that there was the influence of the basic skill approach towards the IPA learning outcomes on the students in 8th of SMPN 11 Yogyakarta in academic year 2015/2016.